Advantages and Disadvantages of Modeling Beliefs by Single Item and Scale Models in the Context of the Theory of Planned Behavior - Benedikt Heuckmann; Marcus Hammann; Roman Asshoff (Education Sciences, 2019)
Teachers’ beliefs about science teaching vary greatly. To analyze the relationships between teachers’ beliefs and other variables related to teaching and learning, researchers can use the following two options: single item belief models or belief scales. In this study, we compared both models in the context of teachers’ beliefs regarding teaching about cancer. Although both models exhibited a good model fit, each approach had both advantages and disadvantages when we judged the modelling approaches in terms of fulfilling the requirements of common psychometric standards and adequately acknowledging the diversity of different beliefs. We discuss the predictive value of both models and their contribution to planning belief-based interventions for cancer education. We argue that researchers should combine the advantages of single item and scale models when analyzing the diversity of teachers’ beliefs.